2011
DOI: 10.1002/ange.201102561
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Azomethine Ylides and Their Complexes: Iridium(III)‐Mediated Cyclization of Nitrone Substrates Containing Alkynes

Abstract: Dem Ruhekomplex auf der Spur: [{IrCp*Cl2}2] katalysiert die Redoxcyclisierung von Nitronalkinen wie 1 unter Bildung von Azomethinyliden, die anschließend mit Elektrophilen und π‐Bindungen umgesetzt werden können. Der ungewöhnliche O‐gebundene Azomethinkomplex 2 wurde isoliert und als Ruhezustand des Katalysators in der Azomethinylid‐Bildung identifiziert. Cp*=C5Me5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Azomethine ylides can be classified as non-stabilized (where R 1 -R 5 = H or alkyl) or stabilized either by electron-withdrawing/electron-donating groups at the appropriate termini of the ylide or by N-metalation [18]. Azomethine ylides are mostly generated in situ due to their high reactivity and/or transient existence; however, in some cases, stabilized ylides have been isolated [19][20][21]. The most frequent type of 1,3-dipolar cycloaddition reaction of azomethine ylides is that with alkenyl or alkynyl dipolarophiles substituted with electron-withdrawing groups, providing access to pyrrolidine-containing molecules of biological [18,[22][23][24][25][26] or materials science interest [27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Azomethine ylides can be classified as non-stabilized (where R 1 -R 5 = H or alkyl) or stabilized either by electron-withdrawing/electron-donating groups at the appropriate termini of the ylide or by N-metalation [18]. Azomethine ylides are mostly generated in situ due to their high reactivity and/or transient existence; however, in some cases, stabilized ylides have been isolated [19][20][21]. The most frequent type of 1,3-dipolar cycloaddition reaction of azomethine ylides is that with alkenyl or alkynyl dipolarophiles substituted with electron-withdrawing groups, providing access to pyrrolidine-containing molecules of biological [18,[22][23][24][25][26] or materials science interest [27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…[3,4] Recently,t he groups of Tang and Li reported that rhodium could also catalyze such an intermolecular alkyne oxidation. [5] Despite these findings, [6] synthetic application of N-oxide-mediated oxidation of alkynes faces two major technical hurdles:1)The carbene intermediate,particularly when generated from an internal alkyne such as ynamide, [7] can undergo over-oxidation which generates unwanted byproducts. [8,4c] 2) Anoble transition-metal catalyst usually is required for optimal reaction efficiency, and may severely limit the practical application of this approach because of the high cost and toxicity of the catalyst.…”
mentioning
confidence: 99%
“…The formation of such bicyclics likely resulted from initial acylation of the nitrone, followed by intramolecular [3+2] dipolar addition. [13] Thus, the reaction pattern is clearly governed by the steric effects of the ortho substituent.…”
Section: Nitrone Directing Groups In Rhodium(iii)-catalyzed C à H Actmentioning
confidence: 99%